Excellent luminous flux of WLEDs with flat dual-layer remote phosphor geometry - Tran Thanh Trang; Phan Xuan Le; Nguyen Doan Quoc Anh (Universitas Ahmad Dahlan, 2019)
This paper focuses on the comparison of the luminous flux of two dual-remote phosphor structures named flat dual-remote phosphor (FDRP) and concave dual-remote phosphor (CDRP). These two configurations have different luminous flux values due to the disparity in scattering properties in white LEDs. However, the researched results showed that FDRP structure is more lucrative than the CDRP structure when it comes to the luminous flux effectiveness. To support the aforementioned idea, this article also presents the influence of the distance between two phosphor layers (d1) and the distance between the phosphor layer with the LED surface (d2) on the optical properties of the FDRP structure. Specifically, the scattering ability and absorption properties of the remote phosphor layer will vary sharply if d1 and d2 are adjusted into different values, which produces an immense impact on the chromatic homogeneity and illumination capability of WLEDs. Therefore, in order to stabilize the correlated color temperature (CCT) of WLEDs at 8500 K when there is a modification on d1 and d2, the concentration of YAG:Ce3+ phosphor also needs to be varied. Accordingly, the scattering process and absorption phenomenon in the remote phosphor layer will bottom out when d1 = d2 = 0, leading to the worst color quality and luminous flux. The effect of the spectra generated as these distances are adjusted is obvious evidence for this point. In other words, the larger the d1 and d2, the larger the scattering surface, and thus the blending of blue and yellow light rays will become more homogeneous, yielding the smallest white light deflection and the lowest luminous flux at the same time. The paper's results indicated that the luminous flux will reach a peak at 1020 lm if d1 = 0.08 mm or d2 = 0.63 mm and the chromatic deflection will hit the lowest point as d1 = 0.64 mm or d2 = 1.35 mm. In the end, manufacturers can make their choice for the production of higher-standard WLEDs based on the general knowledge and helpful information that the article has provided and analyzed.